IMPORTANCE OF THE LEPTIN/GRELIN RATIO AS A BIOMARKER IN DIETARY INDUCED HYPERLIPIDEMIA IN FEMALE C57Black/6 MICE - N. A. Riger; V. S. Evstratova; S. A. Apryatin; I. V. Gmoshinskiy; R. A. Khanferyan (Медицинская иммунология)
Visceral obesity, dyslipidemia and insulin resistance are considered the main causes of metabolic disorders in metabolic syndrome. Leptin and ghrelin are the most important factors involved in regulation of the metabolic processes. The purpose of this study was to evaluate the significance of leptin-to-ghrelin ratio (L/Gh) and cytokine profiles as biomarkers of metabolic and immune disorders in an in vivo model of a dietary induced dyslipidemia in mice.The studies were carried out on 48 female C57Black/6 mice, which were divided into 6 groups of 8 animals. Group 1 (control) received the AIN93 diet; group 2, excess fat administration (30% dry weight); the mice from group 3 were supplied with 20% fructose in drinking water added to the main diet; group 4 got fats and fructose excess, group 5, cholesterol excess (0.5% dry weight); group 6 was fed with cholesterol and fructose in excess. Duration of the experiment was 63 days. In all animals, the relative mass of internal organs was determined. The levels of cytokines, leptin and ghrelin in plasma were determined by means of Luminex 200 analyzer using Bio-Plex kits.There were no significant differences for plasma leptin and ghrelin concentrations between the control and most of experimental groups, except of the 6th group (combined diet with excess fructose and cholesterol) which a significantly lower leptin levels as compared to the controls (group 6: 2.12 pg/ml, min 1.57 – max 3.83 vs group 1: 3.92 pg/ml, min 2.45 – max 27.88, p < 0.05). The changes in plasma ghrelin contents, depending on the diet, showed a generally opposite trend when compared to leptin levels.The value of L/Gh ratio in mice fed with excess fat (group 2) and cholesterol (group 5) showed a statistically unsignificant trend for increase. Fructose added to a diet with fat or cholesterol excess caused a significant decrease in L/Gh ratio (p < 0.05). In animals of the 6th group (fructose + cholesterol) with minimal L/Gh values, the lowest total body fat deposition was found. The relationship between the L/Gh and the fat mass was confirmed by the linear regression relationship between the indicators considered. We have also found a correlation between L/Gh and animal fat weight (r = 0.424, α = 0.004), relative mass of adipose tissue (r = 0.663, α = 0.000), liver (r = -0.315, α = 0.035) and spleen (r = -0.585; α = 0.000), statistically significant correlations between L/Gh, organ and tissue weight and concentrations of IL-12(p40), IL-2, IL-9, IL-13, G-CSF and RANTES. In addition, significant differences were found between the control and test groups for plasma concentrations of G-CSF, IL-12(p40), IL-2, IL-3 and IL-9. The IL-12(p40) concentration in plasma from the group 2 mice was the lowest against controls. Meanwhile, the 6th group exhibited highest IL-12(p40) levels against the lowest L/Gh ratios and total fat levels.Thus, a significant relationship was found between L/Gh ratio and changing mass of organs and tissues, as well as with the levels of cytokines involved into the regulation of inflammation. The most significant relationship was found between the relative mass of body fat, L/Gh ratio and the IL-12(p40) concentration. L/ Gh ratio and IL-12p(40) showed both content Not only a correlation dependence, but also significant changes were noted between the experimental groups in the in vivo model of alimentary dyslipidemia in mice.